2015
DOI: 10.1016/j.physletb.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Tetraquarks as diquark–antidiquark bound systems

Abstract: In this paper, we study four-body systems consisting of diquark-antidiquark, and we analyze diquark-antidiquark in the framework of a two-body (pseudo-point) problem. We solve Lippman-Schwinger equation numerically for charm diquarkantidiquark systems and find the eigenvalues to calculate the binding energies and masses of heavy tetraquarks with hidden charms. Our results are in good agreement with theoretical and experimental data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
0
19
1
Order By: Relevance
“…Choosing a regularization cutoff equal to non zero root of the diquark-antidiquark potential leads to smaller tetraquark masses which are shown with bold numbers in Table II, even with the same regularization cutoff the reported masses in Ref. [1] are different from our results.…”
contrasting
confidence: 83%
See 2 more Smart Citations
“…Choosing a regularization cutoff equal to non zero root of the diquark-antidiquark potential leads to smaller tetraquark masses which are shown with bold numbers in Table II, even with the same regularization cutoff the reported masses in Ref. [1] are different from our results.…”
contrasting
confidence: 83%
“…Clearly the reported results in Ref. [1] can not be trusted, because as it is shown in Table I, not only J = 0 states are not calculated correctly, they have reported the masses for non zero J states, like SĀ±AS √ 2 and AĀ, which cannot be obtained in this formalism. It is a serious challenge and the authors should clarify how this spin-independent formalism can distinguish different spin states and consequently the solution of spin-independent LS integral equation can predict the masses of tetraquarks with non zero total angular momentum.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…We made use of the potential coefficients proposed by Ebert et al We solved Lippmann-Schwinger equation numerically for charm diquark-antidiquark systems and found the eigenvalues to calculate the binding energies and masses of heavy tetraquarks with hidden charms [28].…”
Section: Resultsmentioning
confidence: 99%
“…The main goal of the comment was to show it remains completely unclear, how the authors of Ref. [10] can discriminate between the masses of tetraquarks with axial-vector diquark content and different total angular momentum J in a spin-independent framework. Also it has been shown that the paper suffers from few computational issues, for instance their regularization cutoff is not high enough to achieve accurate results.…”
Section: Introductionmentioning
confidence: 99%